2016
DOI: 10.4049/jimmunol.1502194
|View full text |Cite
|
Sign up to set email alerts
|

FVB/N Mice Spontaneously Heal Ulcerative Lesions Induced by Mycobacterium ulcerans and Switch M. ulcerans into a Low Mycolactone Producer

Abstract: Buruli ulcer, a debilitating disease, is caused by Mycobacterium ulcerans. The incidence of this neglected tropical disease is steadily increasing. As a rule, without treatment, skin ulcers occur and a lengthy healing process may be observed associated with severe functional disabilities. Mouse models are already available to study establishment of lesions or evaluation of therapy but a lack of a suitable animal model, mimicking all clinical stages, in particular the healing process, remains an obstacle to und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 57 publications
3
55
0
Order By: Relevance
“…The principal challenge in this method was the choice of a lysis system resulting in host-cell lysis without damage to the bacterial cells. We recently demonstrated that the mechanical disruption of tissues had no effect on bacterial viability (Marion et al, 2016b). We therefore disrupted the host cells by mechanical lysis and treated them with proteinase K, to digest and degrade the mouse tissue whilst leaving the bacterial cells intact.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The principal challenge in this method was the choice of a lysis system resulting in host-cell lysis without damage to the bacterial cells. We recently demonstrated that the mechanical disruption of tissues had no effect on bacterial viability (Marion et al, 2016b). We therefore disrupted the host cells by mechanical lysis and treated them with proteinase K, to digest and degrade the mouse tissue whilst leaving the bacterial cells intact.…”
Section: Resultsmentioning
confidence: 99%
“…We recently developed the first mouse model for investigating this phenomenon (Marion et al, 2016b). Our investigations have revealed a strong inhibition of mycolactone synthesis during spontaneous healing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations